2012
DOI: 10.1063/1.3702816
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of Ge dangling bonds with different oxygen backbonds at Ge/GeO2 interface

Abstract: Calculations based on the density functional theory predict the formation of gap states near the Ge conduction-band minimum, due to the presence of the dangling bonds of Ge1+ and Ge2+ atoms at the Ge/GeO2 interface. Additionally, gap states near the valence-band maximum appear in the presence of threefold Ge0+ dangling bonds at the Ge/GeO2 interface. To further discuss the electrical property of the GeO2 near the interface, the oxygen-vacancy-related defect in GeO2 is calculated with bulk oxide structure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Oxygen vacancies generated at the GeO 2 /Ge interface diffuse through the oxide toward the surface, where they promote GeO desorption (as evidenced by thermal desorption spectroscopy), leading to the deterioration of the device’s electrical properties . First-principles calculations predicted that these vacancies are likely to be positively charged, resulting in positive fixed charge at the GeO 2 /Ge interface . The instability of the GeO 2 /Ge interface also interferes with the development of devices based on high-k metal oxide/Ge gate stacks, since a GeO x interlayer can be formed during high-k deposition and subsequent thermal treatments. , The synthesis of GeO x layers and control of their properties are also relevant in other applications such as resistive switching memory. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxygen vacancies generated at the GeO 2 /Ge interface diffuse through the oxide toward the surface, where they promote GeO desorption (as evidenced by thermal desorption spectroscopy), leading to the deterioration of the device’s electrical properties . First-principles calculations predicted that these vacancies are likely to be positively charged, resulting in positive fixed charge at the GeO 2 /Ge interface . The instability of the GeO 2 /Ge interface also interferes with the development of devices based on high-k metal oxide/Ge gate stacks, since a GeO x interlayer can be formed during high-k deposition and subsequent thermal treatments. , The synthesis of GeO x layers and control of their properties are also relevant in other applications such as resistive switching memory. , …”
Section: Introductionmentioning
confidence: 99%
“…4 First-principles calculations predicted that these vacancies are likely to be positively charged, resulting in positive fixed charge at the GeO 2 /Ge interface. 5 The instability of the GeO 2 /Ge interface also interferes with the development of devices based on high-k metal oxide/Ge gate stacks, since a GeO x interlayer can be formed during high-k deposition and subsequent thermal treatments. 6,7 The synthesis of GeO x layers and control of their properties are also relevant in other applications such as resistive switching memory.…”
Section: ■ Introductionmentioning
confidence: 99%
“…After FGA, flatband voltage shifts negatively, resulting in positive Nf of 8.5±1.7•10 11 cm -2 . Ab-initio calculations has shown that positive fixed charge density in Ge/GeO2 interfaces is related to oxygen vacancies in GeO2 layer [13]. Oxygen vacancies can possibly be created during the initial gate stack formation, or during FGA due to GeOx reduction by more stable Tm2O3.…”
Section: A Impact Of Forming Gas Anneal On Fixed Charge Densitymentioning
confidence: 99%
“…The structural and electronic properties of Ge=GeO 2 interfaces have been investigated by several groups. 10,11,[16][17][18][19][20][21][22][23][24] Although the residual order at Si=SiO 2 interfaces has been observed by transmission electron microscopy, 25) that at Ge=GeO 2 interfaces has not. Some studies 18,23) use the models in which amorphous GeO 2 is attached to the Ge substrate to investigate electronic structures; however, it is not easy to derive definite conclusions using the models employing amorphous GeO 2 because the model size treated by first-principles calculations is small to eliminate the effect of artificial periodic boundary conditions.…”
Section: Atom Emission From the Interfacementioning
confidence: 99%
“…Some studies 18,23) use the models in which amorphous GeO 2 is attached to the Ge substrate to investigate electronic structures; however, it is not easy to derive definite conclusions using the models employing amorphous GeO 2 because the model size treated by first-principles calculations is small to eliminate the effect of artificial periodic boundary conditions. Therefore, many studies 10,11,16,17,[19][20][21][22]24) adopt the interface atomic structures based on their Si=SiO 2 counterparts, 26) where crystalline GeO 2 is attached to a Ge substrate.…”
Section: Atom Emission From the Interfacementioning
confidence: 99%